Iron Is Filtered by the Kidney and Is Reabsorbed by the Proximal Tubule - Wareing, Mark; Smith, Craig P. (Frontiers in Physiology, 2021)
The aim of this study was to determine the iron (Fe) concentration profile within the lumen of the S2 renal proximal convoluted tubule (PCT) and to resolve whether this nephron segment transported Fe. To do this, we performed in vivo renal micropuncture on Wistar rats, collected PCT tubular fluid from superficial nephrons, and measured Fe concentration. The Fe concentration profile along the S2 PCT suggested significant Fe reabsorption. Proximal tubules were also microperfused in vivo with physiological solutions containing Fe and Zn, Cu, Mn, or Cd. PCTs perfused with 12μmol.l−1 55FeCl3 reabsorbed 105.2±12.7 fmol.mm−1.min−1 Fe, 435±52pmol.mm-1.min−1 Na, and 2.7±0.2nl.mm−1.min−1 water (mean ± SEM; n=19). Addition of ascorbate (1mmol.l−1) to the perfusate did not significantly alter Fe, Na, or water reabsorption. Supplementing the control perfusate with 60μmol.l−1 FeSO4 significantly decreased 55Fe uptake. Recalculating for the altered molar activity following addition of unlabeled Fe revealed a three-fold increase in Fe flux. Addition to the perfusate 12μmol.l−1 CuSO4, MnSO4, CdSO4, or ZnSO4 did not affect Fe, Na, or water flux. In conclusion, (1) in vivo, S2 PCTs of rat reabsorb Fe and (2) Fe is reabsorbed along the PCT via a pathway that is insensitive to Cu, Mn, Cd, or Zn. Together, these data demonstrate for the first time the hitherto speculated process of renal Fe filtration and subsequent tubular Fe reabsorption in a living mammal.